Influence Investment Decisions, Financing and Dividend Policy of the Company's Value in the Food and Beverage Company Listed in Indonesia Stock Exchange - Nuramalia, Amalia (Patria Artha Journal of Accounting dan Financial Reporting, 2017)
The purpose of this study was to: 1) analyze the influence investment decisions, financing, and dividend policy on firm value on food and beverage companies listed in Indonesia Stock Exchange; and 2) determine which variables are the dominant influence on the value of the company in the food and beverage companies listed in Indonesia Stock Exchange. Methods of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS program. The results showed that simultaneous and partial test showed variable investment decisions, financing decisions and dividend policy significant and positive impact on corporate value on food and beverage companies listed in Indonesia Stock Exchange. Variable dividend policy of the dominant influence on the value of the company in food and beverage companies listed in Indonesia Stock Exchange, as the figure or standardized coefficient beta greater than other variables. This means that the second hypothesis of this study is not proven.